Discovery of Histone Deacetylase Inhibitor Using Molecular Modeling and Free Energy Calculations - Mishra A.; Singh A. (My University, 2025)
The histone acetylation-deacetylation at lysine regulates the functions of many cellular proteins. An increased expression of HDAC6 can cause an increased amount of deacetylated histones, which leads to an inhibition of gene expression and has been associated with cancer cell proliferation. The present study screened the ZINC database to find novel HDAC6 inhibitors using virtual high-throughput screening techniques. The docking score, free energy, and binding pattern of the complexes were used to select a best ligand for further study. Molecular dynamic simulations, binding interactions, and the stability of docked conformations were investigated. Several parameters that determine protein-ligand interactions, such as root-mean-square deviation (RMSD), root-mean-square fluctuation (RMSF), radius of gyration (Rg), and binding pattern, were observed. Hydrogen bonds were observed at His 573 and Gly 582 after a 150 ns simulation with identified compound ZINC000002845205, and they were similar to known inhibitor Panobinostat. The molecular mechanics with generalised Born and surface area solvation (MM/GBSA) free energy was comparable to known inhibitor Panobinostat. ZINC000002845205 qualifies drug-likeness according to Lipinski's rule-of-five, rule-of-three, and the World Drug Index (WDI)-like rule, but there is one violation in the lead-like rule. © 2022 The Authors.